THE ROLE OF ENVIRONMENTAL LAW IN SUSTAINABLE DEVELOPMENT TO REALIZE COMMUNITY WELFARE AND ENVIRONMENTAL JUSTICE - Alan Musyafaan; Mas Subagyo Eko Prasetyo (Fox Justi : Jurnal Ilmu Hukum, 2021)
for life in all its aspects and dimensions in accordance with the insight of the archipelago. In order to utilize natural resources to promote public welfare as mandated in the 1945 Constitution of the Republic of Indonesia and to achieve a happy life, sustainable development with an environmental perspective, based on an integrated and comprehensive national policy taking into account the needs of the present generation and future generations. For this reason, it is necessary to consider implementing a harmonious, harmonious, and balanced environmental management in order to support the implementation of sustainable development with an environmental perspective. In implementing the protection and management of the environment in the context of sustainable development with an environmental perspective, it is necessary to pay attention to the level of public awareness and the development of the global environment as well as international legal instruments related to the environment. Public awareness and life in relation to environmental protection and management has developed in such a way that it needs to be perfected to achieve sustainable development goals with an environmental perspective. The regulations stipulated in Law no. 32 of 2009 concerning Environmental Protection and Management, especially in Chapter VII that the management of hazardous and toxic materials as well as hazardous and toxic waste materials must be carried out, in order to minimize the waste disposal system with very little risk for the environment, human survival and other living things. By realizing this, hazardous and toxic materials and their waste need to be protected and managed properly.his research was conducted through the juridical-normative method, where the study of the approach used a conceptual approach. The purpose of this study is to find out how far the influence of the Sustainable Development Goals (SDGs) applied to the environment is, whether it is as expected or vice versa, and to see the influence of environmental law which is the legal basis for this research in solving problems related to this. . And of course with the SDGs, many things must be available, namely the existence of pillars that must exist accompanied by institutions that become the necessary background, in terms of economics, politics, culture, and related bureaucracies.